Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have:

$f(x) = 0.1\delta(x-2) +0.4\delta(x-1) +{1 \over 4}e^{-|x|}$

$Y=g(x)=0, x\le0$
$g(x)=x^2, 0<x<1$
$g(x)=1, x\gt1$

The task is to find the pdf (density function) of y.

$P(Y=0)=P(X<0)=\int_{-\infty}^0f(x)dx=\int_{-\infty}^0{1 \over 4}e^{x}$
Since the diracs are all zero in the interval and -|x|=x in the interval. thus $f(y)= {1 \over 4}\delta(y)$ is one component of the resulting f(y)

$P(Y=1)=\int_1^{\infty}f(x)dx=\int_1^{\infty}0.1\delta(x-2) +\int_1^{\infty}0.4\delta(x-1)+\int_1^{\infty}{1 \over 4}e^{-x}$
$=0.1+0.4+{1 \over 4}e^{-1}=0.5919698603$
thus $f(y)= (0.5+{1 \over 4}e^{-1})\delta(y-1)$ is one component of the resulting f(y)

finally i evaluate the problem for $0<x<1$ if find fy by the formula:
$f(y)=\Sigma_0^1 {f(xi) \over |g'(x_i)|}$

$g'(x)=2x$
$x_i=y-g(x)$
$x_1=\sqrt y$
$x_2=-\sqrt y$

$f(y)={1 \over {4 |2*-\sqrt y|}}e^{-|-\sqrt y |}+{1 \over {4 |2\sqrt y|}}e^{-|\sqrt y |}$
$={2 \over {4 |2\sqrt y|}}e^{-|\sqrt y |}={1 \over {4 |\sqrt y|}}e^{-|\sqrt y |}$

thus the pdf of y is ${1 \over {4 |\sqrt y|}}e^{-|\sqrt y |}$ for $0<y<1$

evaluating $\int_0^1f(y)dy$ yields:
$-{1 \over 2}e^{-|1|}-(-{1 \over 2}e^{-|0|})=0.31606$

If we add the areas under the full pdf f(y) together, we get an area under the whole pdf that is:
$0.5919698603+0.31606+0.25=1.15$

As one can see this does not add up to one, and i clearly has misunderstood something in the definition of how to calculate Y=g(x).

Edit: The pdf, of y, that i find is:
$f(y)={1 \over {4 |\sqrt y|}}e^{-|\sqrt y |}+(0.5+{1 \over 4}e^{-1})\delta(y-1)+{1 \over 4}\delta(y)$

But the integral $\int_{-\infty}^{\infty}f(y)dy \ne 1$

Since i have checked my calculations several times, i must have misunderstood something about how to find the pdf of y for the given pdf of x, f(x), and the given Y= g(x).

Edit 2: Could it be that the root $x_2=-\sqrt y$ is not valid in the interval so the result $f(y)={1 \over {4 |2*-\sqrt y|}}e^{-|-\sqrt y |}+{1 \over {4 |2\sqrt y|}}e^{-|\sqrt y |}$ should actually be:
$f(y)={1 \over {4 |2\sqrt y|}}e^{-|\sqrt y |}$

share|improve this question
    
$f(x)$ is the density of a mixed distribution, a standard Laplace distribution with probability $0.5$ and two points of positive probability. $g(x)$ is the cumulative distribution of a triangular distribution. But I do not see what the question is. Perhaps you are looking for the distribution of $g(X)$ where $X$ has $f(x)$ as its density? –  Henry Feb 19 '12 at 11:31
    
You are making a sign error when you find $$\int_1^\infty \frac{1}{4}e^{-x}\mathrm dx = -\frac{1}{4}e^{-1}.$$ The integral of a positive function should be positive. –  Dilip Sarwate Feb 19 '12 at 15:54
    
Think i found the issue, see "Edit2" –  jwmbrg Feb 19 '12 at 16:15
add comment

1 Answer 1

up vote 0 down vote accepted

The standard method applies, as usual. To wit:

Let $u$ denote any bounded measurable function, then $\mathrm E(u(Y))=\mathrm E(u(g(X))$ hence $$ \mathrm E(u(Y))=u(0)\mathrm P(X\leqslant0)+\int_0^1u(x^2)\frac14e^{-x}\mathrm dx+u(1)\mathrm P(X\geqslant1). $$ One computes $$ \mathrm P(X\leqslant0)=\int_{-\infty}^0\frac14\mathrm e^x\mathrm dx=\frac14, $$ and $$ \mathrm P(X\geqslant1)=0.1+0.4+\int_1^{+\infty}\frac14\mathrm e^{-x}\mathrm dx=0.5+\frac14\mathrm e^{-1}. $$ In the continuous part, the change of variable $y=x^2$, $\mathrm dy=2x\mathrm dx=2\sqrt{y}\mathrm dx$, yields $$ \int_0^1u(x^2)\frac14\mathrm e^{-x}\mathrm dx=\int_0^1u(y)\frac14\mathrm e^{-\sqrt{y}}\frac1{2\sqrt{y}}\mathrm dy. $$ Finally, $$ \mathrm E(u(Y))=\frac14u(0)+\int_0^1u(y)\frac18\mathrm e^{-\sqrt{y}}\frac1{\sqrt{y}}\mathrm dy+\left(\frac12+\frac14\mathrm e^{-1}\right)u(1), $$ for every bounded measurable $u$ hence the distribution $\mathrm P_Y$ of $Y$ is $$ \mathrm P_Y(\mathrm dy)=\frac14\delta_0(\mathrm dy)+\frac18\mathrm e^{-\sqrt{y}}\frac1{\sqrt{y}}[0\lt y\lt1]\mathrm dy+\left(\frac12+\frac14\mathrm e^{-1}\right)\delta_1(\mathrm dy). $$ Sanity check: The mass of the Dirac at $0$ part is $\frac14$, the mass of the continuous part is $\frac14(1-\mathrm e^{-1})$ and the mass of the Dirac at $1$ part is $\frac12+\frac14\mathrm e^{-1}$, hence the total mass is $1$. We happy.

share|improve this answer
    
So yes, your Edit2 points at the problem with your first solution. –  Did Feb 19 '12 at 17:33
1  
Not enough reputation, so no upvote, but i find the approach you propose, for the change of variable, much more intuitive than the one given in my litterature. –  jwmbrg Feb 19 '12 at 17:51
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.